Weight Lifting Trajectory Optimization for Variable Stiffness Actuated Robot. (18th July 2019) - Ji, Chen; Kong, Minxiu; Li, Ruifeng
Abstract : Variable stiffness actuator is a new actuation of robot which is inspired by motor control of human arm. And it is promising way to exploit the human-like performance and human-like motion. However, due to the mechanical complexity and redundancy of the actuators, it is not trivial to control the variable stiffness actuated robot to perform a human-like motion. In this paper, the weight lifting problem with variable stiffness actuated robot is studied. Then, the original problem is formulated as a constrained optimal control problem and transformed as a general nonlinear programming problem with Gauss pseudospectral method. Simulation studies demonstrate the effectiveness of the proposed method compared with the iLQR approach. Furthermore, the simulations results are presented to show the influence of stiffness variation of variable stiffness actuators on the weight lifting problem.